ヒガシナンキョクタイリク Sandercock Nunatakグン ニオケル チガク チョウサ ニツイテ ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 渡辺, 興亜; ワタナベ, オキツグ; 吉村, 愛一郎; ヨシムラ, アイイチロウ; WATANABE, Okitsugu; YOSHIMURA, Aiichiro (国立極地研究所, 1972)
P(論文) Sandercock Nunataks are located at lat. 68°36'41"S and long. 52°06'02"E about 500km east of Syowa Station. These nunataks were visited by the JARE 11 traverse party in the summer of 1970. Sandercock Nunataks are composed of four nunataks temporarily named A, B, C and D from north to south. The following survey and observation were carried out. 1. Determination of the location of each nunatak by astronomical surveying and sketch mapping. 2. Geophysical measurements : Measurements of geodetic gravity and geomagnetism in the vicinity of the nunataks. 3. Geological observations : Geological sketch mapping for each nunatak and sampling of rocks. 4. Glaciological observations : Observations of the occurrence of inland ice and patterned ground with ground ice on the nunataks. departmental bulletin paper